The Effect of Allocation Fund and Regional Revenue on Fiscal Independence: Evidence from Murung Raya - Fitriadi; Miar; Alexandra Hokum (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
This study analyzes the effect of locally generated revenue, general allocation funds, and special allocation funds in improving regional fiscal independence in Murung Raya Regency, Central Kalimantan, Indonesia. Despite more than two decades of fiscal decentralization, the regency still shows very low fiscal independence, with own-source revenue contributing less than 11% of total revenue while dependence on central government transfers exceeds 88%. The objective is to empirically examine which revenue component truly drives fiscal independence using quarterly data from 2018 to 2024. The research applies descriptive statistics, fiscal ratio analysis, and multiple linear regression on 28 quarterly observations. The results show that only locally generated revenue has a significant positive effect on the fiscal independence ratio, while general allocation funds and special allocation funds have no significant impact. The regression model explains 82% of the variation in fiscal independence and fulfills all classical assumption tests. The study concludes that increasing fiscal independence in Murung Raya Regency can only be achieved by strengthening locally generated revenue through better exploitation of local economic potential, tax administration reform, and institutional improvement. Relying on transfer funds, regardless of their size, will not reduce fiscal dependence or create sustainable regional autonomy.